2009
DOI: 10.1080/03630260802683377
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for a Rare β0-Thalassemia Mutation [Frameshift Codons 25/26 (+T)] Causes β-Thalassemia Intermedia in an Iranian Family

Abstract: The severity of beta-thalassemia (beta-thal) is remarkable for its variability in different populations, even in different patients. We studied a family from Azerbaijan Province, Northwestern Iran, who had a rare beta(0)-thal mutation, namely the frameshift codons (FSC) 25/26 (+T), originally reported in Tunisia. Unlike the Tunisian family, in our family the mutation was a beta(0) type and the affected members were dependent and independent of blood transfusions. This mutation was linked to the -158 (C>T) poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 6 The severity of β-thalassemia is remarkable for its variability in different populations, even in different patients. 13 The 158(C-T) polymorphism of the Gγ-globin gene (Xmnl polymorphism) is known to ameliorate the severity of the disease because of its strong association with an increased production of HbF. 2 , 3 HbF production can partially compensate for the lack of adult hemoglobin (HbA) in patients with β-thalassemia major or intermedia.…”
Section: Discussionmentioning
confidence: 99%
“… 6 The severity of β-thalassemia is remarkable for its variability in different populations, even in different patients. 13 The 158(C-T) polymorphism of the Gγ-globin gene (Xmnl polymorphism) is known to ameliorate the severity of the disease because of its strong association with an increased production of HbF. 2 , 3 HbF production can partially compensate for the lack of adult hemoglobin (HbA) in patients with β-thalassemia major or intermedia.…”
Section: Discussionmentioning
confidence: 99%
“…CD25/26, which originally is a Tunisian mutation, is among the rarest mutations in Iran. It was introduced by Haghi et al in 2009 in Tabriz, East Azerbaijan province, Iran ( 13 ). In this study, this mutation was identified in five out of 1541 subjects (0.33%).…”
Section: Discussionmentioning
confidence: 99%
“…In each province, some of these mutations are categorized as common, while others are known to be rare. Collectively, in the 30 provinces of Iran, 13 mutations encompass 70-90% of the patients with β-thalassemia these mutations are classified as common (4,8,(13)(14)(15)(16). The majority of the mutations are single nucleotide substitutions or point mutations.…”
Section: Diversity Among the Rare β-Globin Variants In Iranmentioning
confidence: 99%